2017
DOI: 10.1159/000484168
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed Adiponectin Levels and Increased Adiponectin Response to Oral Glucose Load in Lean Women with Severe Acne Normalizes after Isotretinoin Treatment

Abstract: ide and adiponectin levels. Glucose metabolism markers in patients with acne and controls were similar at baseline and did not change after treatment. Baseline OGTT in acne patients revealed an increased adiponectin response at 2 h, which was not present in healthy controls. Remarkably, this OGTT-induced adiponectin increment in acne patients was diminished after isotretinoin treatment. Conclusion: Adiponectin levels are differently regulated in women with severe acne and healthy controls in that circulating b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 27 publications
3
27
0
2
Order By: Relevance
“…This came in accordance with Aydin et al (4) who demonstrated that, patients with acne vulgaris had significantly lower serum adiponectin levels than controls. Similarly, Çerman et al (15) have conducted their study on a total of 50 patients with acne vulgaris and 36 healthy control subjects.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This came in accordance with Aydin et al (4) who demonstrated that, patients with acne vulgaris had significantly lower serum adiponectin levels than controls. Similarly, Çerman et al (15) have conducted their study on a total of 50 patients with acne vulgaris and 36 healthy control subjects.…”
Section: Discussionsupporting
confidence: 92%
“…The roles of adipokines in regulating inflammatory responses in adipose tissues and systemic organs become evident during the development of obesity and in response to infection or systemic inflammation. An increasing number of studies have identified the relationship between various adipokines and multiple cutaneous diseases (4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…They revealed increased adiponectin response to oral glucose tolerance test at 2 h in acne patients but this effect was lost after isotretinoin treatment. In this study, it was suggested that isotretinoin treatment restores dysregulation of adiponectin dynamics in severe acne (24).…”
Section: Discussionmentioning
confidence: 81%
“…Although some papers demonstrated that there was no significant difference between circulating leptin, adiponectin, and RBP4 levels in patients with acne vulgaris, others found higher leptin and lower adiponectin serum concentrations [193][194][195][196]. Interestingly, isotretinoin (the most effective anti-acne agent) altered adiponectin levels and decreased leptin levels, which were…”
Section: Acne Vulgarismentioning
confidence: 99%